2010
DOI: 10.1029/2009jb007171
|View full text |Cite
|
Sign up to set email alerts
|

A buried volcano in the Calabrian Arc (Italy) revealed by high‐resolution aeromagnetic data

Abstract: [1] Aeromagnetic data collected between the Aeolian volcanoes (southern Tyrrhenian Sea) and the Calabrian Arc (Italy) highlight a WNW-ESE elongated positive magnetic anomaly centered on the Capo Vaticano morphological ridge (Tyrrhenian coast of Calabria), characterized by an apical, subcircular, flat surface. Results of forward and inverse modeling of the magnetic data show a 20 km long and 3-5 km wide magnetized body that extends from sea floor to about 3 km below sea level. The magnetic properties of this bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
26
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 66 publications
5
26
1
Order By: Relevance
“…The overall low intensity and the wavelength of the observed magnetic anomalies are consistent with the weak magnetization of exposed crystalline and sedimentary rocks (Cifelli et al, 2007;De Ritis et al, 2010;Macrì et al, 2014;Mattei et al, 1999Mattei et al, , 2002. In turn, the weak magnetic anomaly values in the investigated area are in agreement with results of previous magnetic surveys of the same region (Agip SpA Italia, 1981;Caratori Tontini et al, 2004;Chiappini et al, 2000).…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…The overall low intensity and the wavelength of the observed magnetic anomalies are consistent with the weak magnetization of exposed crystalline and sedimentary rocks (Cifelli et al, 2007;De Ritis et al, 2010;Macrì et al, 2014;Mattei et al, 1999Mattei et al, , 2002. In turn, the weak magnetic anomaly values in the investigated area are in agreement with results of previous magnetic surveys of the same region (Agip SpA Italia, 1981;Caratori Tontini et al, 2004;Chiappini et al, 2000).…”
Section: Resultssupporting
confidence: 81%
“…Both scattered magnetic measurements of the Hercynian basement (De Ritis et al, 2010) and systematic magnetic analyses of the Miocene-Pleistocene marine clays (Cifelli et al, 2007;Mattei et al, 1999Mattei et al, , 2002Macrì, Speranza, & Capraro, 2014) revealed very low magnetic susceptibility values in the order of 1-2 × 10 −4 SI.…”
Section: Geological Settingmentioning
confidence: 99%
“…Previously published aeromagnetic data (De Ritis et al, 2010b) have been reprocessed in order to obtain a better extraction of the CV anomaly out off the regional magnetic field. Indeed, the anomaly and its -Reduced to The Pole‖ (hereafter RTP) transformation (Baranov and Naudy 1964, e.g., RTP-CV-anomaly) display an extension forming a tail of several kilometres to the east and northeast (Figs.…”
Section: Aeromagnetic Data Processingmentioning
confidence: 99%
“…Here we use recently acquired high resolution aeromagnetic data over Adelaide Island, on the western margin of the AP (Figs 1 and 2), to investigate the processes occurring along the arc/forearc boundary. High resolution aeromagnetic data has elsewhere been used to reveal tectonic structures in forearc regions (Ponce et al 2003;Saltus et al 2005), the geometry of arc magmatic intrusions (De Ritis et al 2010), and tectonic and magmatic patterns in rift systems formed along the reactivated margins of older magmatic arc terranes (Ferraccioli et al 2005). We apply digital enhancement, 2-D modelling and 3-D inversion to the new magnetic data in order to reveal the structure of the AP arc/forearc boundary.…”
Section: Introductionmentioning
confidence: 99%